Perceptions and experiences of family caregivers of bedridden elderly - Dantas, Ticiano Magalhães (2015)
Objective: To know the perceptions and experiences of family caregivers of bedridden elderly. Methods: A qualitative descriptive exploratory study conducted in January 2015 with four caregivers in a Family Health Center in the municipality of Araripe, CE. Data were collected through semi-structured interviews and the information was organized using the content analysis technique. A total of three categories emerged from the analysis of the reports of caregivers: the dependence process of the elderly; daily difficulties experienced by the caregiver; and satisfaction with the home care service. Results: The dependence process of the elderly took place as a consequence of pathological processes such as neoplasm, cerebrovascular accident and dementia. However, it could also be observed that physiological phenomena – common in old age – can also make individuals dependent on caregivers. As to the difficulties faced by the caregivers, they reported the need for greater involvement by the family, given that the centralization of work generates an overload and hence affects the care of the elderly. Teamwork in the home care context is fundamental, given that it allows a complementary and comprehensive care to the elderly/caregiver binomial. Conclusion: Healthy aging is a major challenge to be overcome given that the development of a healthy lifestyle is difficult in all social strata. It is necessary to improve home care in order to provide support to caregivers so that the quality of life of bedridden elderly and caregivers is improved.